Bacteremia Prevention during Periodontal Treatment-An In Vivo Feasibility Study - Patrick Jansen; Georg Conrads; Johannes-Simon Wenzler; Felix Krause; Andreas Braun (MDPI AG, 2023)
The link between periodontitis and systemic diseases has increasingly become a focus of research in recent years. In this context, it is reasonable-especially in vulnerable patient groups-to minimize bacteremia during periodontal treatment. The aim of the present in vivo feasibility study was to investigate the possibility of laser-based bacteremia prevention. Patients with stage III, grade B generalized periodontitis were therefore treated in a split-mouth design either with prior 445 nm laser irradiation before nonsurgical periodontal therapy or without. During the treatments, clinical (periodontal measures, pain sensation, and body temperature), microbiological (sulcus samples and blood cultures before, 25 min after the start, and 10 min after the end of treatment), and immunological parameters (CRP, IL-6, and TNF-α) were obtained. It was shown that periodontal treatment-related bacteremia was detectable in both patients with the study design used. The species isolated were Schaalia georgiae, Granulicatella adiacens, and Parvimonas micra. The immunological parameters increased only slightly and occasionally. In the laser-assisted treatments, all blood cultures remained negative, demonstrating treatment-related bacteremia prevention. Within the limitations of this feasibility study, it can be concluded that prior laser disinfection can reduce bacteremia risk during periodontal therapy. Follow-up studies with larger patient numbers are needed to further investigate this effect, using the study design presented here.